Male breast cancer - a review on risk factors, tumor characteristics, diagnostics and treatment - Martyna Maria Zielińska; Jakub Aleksandrowicz; Natalia Zarankiewicz; Julia Kuchnicka; Katarzyna Kosz; Aleksandra Kuchnicka; Klaudia Sapuła; Klaudia Remjasz; Wojciech Siedlecki; Mateusz Fabiś (Kazimierz Wielki University, 2022)
Introduction and purpose: Male breast cancer (MBC) is estimated to less than 1% of all breast cancer cases worldwide. A lifetime risk of developing MBC amounts to 1:1000. The data on breast cancer in men is limited. This review aims to analyze information on risk factors, diagnostics and treatment in men suffering from breast cancer.  Material and method: This review was based on available data collected in PubMed and published in the years 2001-2022. The research was done by looking through keywords as follows: "breast cancer", "male breast cancer", "risk factors" and "treatment". Results: Male breast cancer usually manifests as a painless, retroareolar mass in the breast. Risk factors include advanced age, hormonal imbalance, exposure to radiation and a positive family history. A significant risk increase in MBC development occurs in BRCA2, CHEK2, PALB2 and ATM genes mutations. G2 ductal carcinoma with no special type is most often diagnosed. Dominating subtype is luminal A cancer, while HER2 protein overexpression is extremely rare. Radical mastectomy or breast conserving therapy remain surgical therapeutic options. The most preferred endocrine therapy is tamoxifen. The choice of chemotherapy in men is based on the same criteria as in women.  Conclusions: Delayed diagnosis and tumor characteristics are associated with a much worse prognosis for men compared to women. Therefore, further clinical research is crucial in order to improve the diagnostic possibilities and treatment targeted at men with this type of cancer.